Study of reading habits 1989 - Southeastern Skåne - Weibull, Lennart (University of Gothenburg, 1993)
This survey forms part of the research program 'Dagspresskollegiet'. The target group of this survey was the inhabitants of five municipalities in Southeast Skåne: Sjöbo, Skurup, Simrishamn, Tomelilla and Ystad. Most of the questions are replications of questions asked in previous readership studies, i.e. questions concerning reading habits, subscriptions of papers, reading interests and background variables such as gender, age, education and party preference. There were also a number of questions not asked in previous surveys, such as the importance of having many pictures, illustrations, maps etc. in the daily paper. The respondent also had to compare the two local papers Ystad Allehanda and Skånska Dagbladet with regard to a number of qualities. A battery of questions dealt with the local paper Ystad Allehanda specifically. The respondents also had to indicate the importance of a number of ethical rules for the morning press and evening press respectively. Another question dealt with the respondents´ activities during the last twelve months.

Denna undersökning ingår i forskningsprogrammet 'Dagspresskollegiet'. Studiens målgrupp var invånarna i fem kommuner i sydöstra Skåne: Sjöbo, Skurup, Simrishamn, Tomelilla och Ystad. Huvuddelen av frågorna i undersökningen är identiska med frågor ställda i tidigare lokala läsvaneundersökningar. Till dessa hör frågor som rör läsvanor, tidningsprenumerationer och läsintressen, samt bakgrundsfrågor såsom kön, ålder, utbildning och partisympati. Ett antal frågor om vikten av att ha många bilder, illustarationer, kartor, etc. i en dagstidning, har inte ställts i tidigare undersökningar. Respondenten fick även jämföra de två lokala tidningarna Ystad Allehanda och Skånska Dagbladet beträffande ett antal egenskaper. En serie frågor avsåg Ystad Allehanda specifikt. Respondenterna fick även ange betydelsen av ett antal etiska regler för morgon- respektive kvällspress. Andra frågor berörde respondenternas aktiviteter under de senaste tolv månaderna.
Läsvanestudien 1989 - Sydöstra Skåne
Keywords: internal politics; inrikespolitik; Media; Media; Political behaviour and attitudes; Politiska beteenden och attityder; Leisure, tourism and sport; Fritid, turism och sport; Social Sciences; Samhällsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap